Wild griffon vultures (Gyps fulvus) fed at supplementary feeding stations: Potential carriers of pig pathogens and pig‐derived antimicrobial resistance?. Issue 3 (13th January 2020) - Sevilla, Eloísa; Marín, Clara; Delgado‐Blas, José F.; González‐Zorn, Bruno; Vega, Santiago; Kuijper, Ed; Bolea, Rosa; Mainar‐Jaime, Raúl C.
Abstract: The carriage of two important pathogens of pigs, that is enterotoxigenic Escherichia coli (ETEC) and Clostridioides difficile, was investigated in 104 cloacal samples from wild griffon vultures ( Gyps fulvus ) fed on pig carcasses at supplementary feeding stations (SFS), along with their level of antimicrobial resistance (AMR). E. coli was isolated from 90 (86.5%) samples, but no ETEC was detected, likely because ETEC fimbriae confer the species specificity of the pathogen. Resistance to at least one antimicrobial agent was detected in 89.9% of E. coli isolates, with AMR levels being extremely high (>70%) for tetracycline and streptomycin and very high (>50%) for ampicillin and sulfamethoxazole–trimethoprim. Resistance to other critically important antimicrobials such as colistin and extended‐spectrum cephalosporins was 2.2% and 1.1%, respectively, and was encoded by the mcr‐1 and bla SHV‐12 genes. Multidrug resistance was displayed by 80% of the resistant E. coli, and bla SHV‐12 gene shared plasmid with other AMR genes. In general, resistance patterns in E. coli from vultures mirrored those found in pigs. Clostridioides difficile was detected in three samples (2.9%); two of them belonged to PCR ribotype 078 and one to PCR ribotype 126, both commonly found in pigs. All C. difficile isolates were characterized by a moderate‐to‐high level of resistance to fluoroquinolones and macrolides but susceptible to metronidazole or vancomycin, similar to what is usually found in C. difficile isolates from pigs. Thus, vultures may contribute somewhat to the environmental dissemination of some pig pathogens through their acquisition from pig carcasses and, more importantly, of AMR for antibiotics of critical importance for humans. However, the role of vultures would likely be much lesser than that of disposing pig carcasses at the SFS. The monitoring of AMR, and particularly of colistin‐resistant and ESBL‐producing E. coli, should be considered in pig farms used as sources of carcasses for SFS.